2020
DOI: 10.1186/s12884-020-2814-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal sleep duration and quality, and the risk of preterm birth: a systematic review and meta-analysis of observational studies

Abstract: Background: To assess the association of sleep duration and quality with the risk of preterm birth. Methods: Relevant studies were retrieved from the PubMed and Web of Science databases up to September 30, 2018. The reference lists of the retrieved articles were reviewed. Random effects models were applied to estimate summarized relative risks (RRs) and 95% confidence intervals (CIs). Results: Ten identified studies (nine cohort studies and one case-controlled study) examined the associations of sleep duration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 54 publications
0
26
0
3
Order By: Relevance
“…Researchers have reported that poor sleep quality increases the risk of systemic inflammation, 4 preterm birth, 5,6 longer labour, 7 unplanned caesarean section, 7 gestational diabetes mellitus (GDM), 8,9 depression during both the prenatal and postpartum periods and suicide among pregnant women. [10][11][12] Fortunately, good management of poor sleep during pregnancy can improve maternal and neonatal health.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported that poor sleep quality increases the risk of systemic inflammation, 4 preterm birth, 5,6 longer labour, 7 unplanned caesarean section, 7 gestational diabetes mellitus (GDM), 8,9 depression during both the prenatal and postpartum periods and suicide among pregnant women. [10][11][12] Fortunately, good management of poor sleep during pregnancy can improve maternal and neonatal health.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, given to inconsistency in the definition of long sleep duration in previous studies [ 42 ], we also performed the same analyses using ≥10 h of sleep per day as excessive sleep duration and found that sleep duration ≥10 h/day had similar effects on CD after adjusting for confounding factors (OR:1.18, 95%CI:1.08–1.29). Excessive sleep duration increased risk of a number of pregnancy complications such as GDM [ 34 ], preeclampsia and hypertension [ 17 ], late stillbirth [ 43 ], and preterm birth [ 44 ]. Therefore, avoiding excessive sleep duration might be an important antenatal practice not only to lower the risk of CD but also to reduce other pregnancy complications such as GDM [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have evaluated the impact of CPAP in pregnancy [ 42 ], particularly as it relates to perinatal mood. In addition, barriers to CPAP treatment in pregnancy include risk for poor adherence, which may be secondary to baseline poor sleep [ 3 ] or demands of childcare and other responsibilities that may take precedence over their health. Future research on the effects of early CPAP usage on prenatal depressive symptoms is warranted given the findings in this study and the challenges associated with treating SDB in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality worsens during pregnancy [ 1 , 2 ], and poor sleep in pregnancy is associated with adverse outcomes of pre-term birth [ 3 ], longer labor and delivery time [ 4 , 5 ], and postpartum depressive symptoms [ 1 ]. Sleep disordered breathing (SDB)—a spectrum of disorders characterized by interruptions in airflow due to obstruction of the upper airway that leads to fragmented sleep and diminished sleep quality—can disrupt sleep in expectant mothers.…”
Section: Introductionmentioning
confidence: 99%